Quantitative easing, bond risk premia and the exchange rate in a small open economy - Jens H. E. Christensen; Xin Zhang (Sveriges Riksbank, 2024)
We assess the impact of large-scale asset purchases, commonly known as quantitative easing (QE), conducted by Sveriges Riksbank and the European Central Bank (ECB) on bond risk premia in the Swedish government bond market. Using a novel arbitrage-free dynamic term structure model of nominal and real bond prices that accounts for bondspecific safety premia, we find that Sveriges Riksbank's bond purchases raised inflation and short-rate expectations, lowered nominal and real term premia and inflation risk premia, and increased nominal bond safety premia, suggestive of signaling, portfolio rebalance, and safe asset scarcity effects. Furthermore, we document spillover effects of ECB's QE programs on Swedish bond markets that are similar to the Swedish QE effects only after controlling for exchange rate fluctuations, highlighting the importance of exchange rate dynamics in the transmission of QE spillover effects.
Keywords: C32; E43; E52; E58; F41; F42; G12; 330; term structure modeling; financial market frictions; safety premium; unconventional monetary policy